2014
DOI: 10.1186/1471-2431-14-83
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of predicting in-hospital mortality in critically ill children by assessing blood lactate levels at admission

Abstract: BackgroundHyperlactatemia upon admission is a documented risk factor for mortality in critically ill adult patients. However, the predictive significance of a single lactate measurement at admission for mortality in the general population of critically ill children remains uncertain. This study evaluated the predictive value of blood lactate levels at admission and determined the cut-off values for predicting in-hospital mortality in the critically ill pediatric population.MethodsWe enrolled 1109 critically il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
63
1
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 29 publications
10
63
1
8
Order By: Relevance
“…Also in one large cohort study where serum albumin was one of the covariates in the regression analysis, hypoalbuminemia was a significant predictor of mortality in critically ill children. 18 The present study also showed that serum albumin level at admission was an important discriminator of mortality with an AUC of 0.694. In contrast; Durward et al 3 reported that the discriminatory ability of serum albumin level at admission was poor for detecting PICU mortality.…”
Section: Discussionmentioning
confidence: 57%
“…Also in one large cohort study where serum albumin was one of the covariates in the regression analysis, hypoalbuminemia was a significant predictor of mortality in critically ill children. 18 The present study also showed that serum albumin level at admission was an important discriminator of mortality with an AUC of 0.694. In contrast; Durward et al 3 reported that the discriminatory ability of serum albumin level at admission was poor for detecting PICU mortality.…”
Section: Discussionmentioning
confidence: 57%
“…Among undifferentiated children with SIRS, early hyperlactataemia is significantly associated with increased risk of organ dysfunction, resuscitative therapies and critical illness. [19] Upon multiple logistic regression analysis, lactate level (OR= 1.057) was found to be significantly associated with mortality (p= 0.019); however, the association of core to peripheral temperature gradient with mortality was not found to be significant (p= 0.476).…”
Section: Discussionmentioning
confidence: 93%
“…Past studies suggest that PRISM III can predict deaths and clinical outcomes in children [14][15][16] . The optimal cut-off level of lactate for predicting in-hospital mortality in critically ill children as per the study by Zhenjiang Bai et al was blood lactate level of 5.55 mmol/l (49.5 mg/dl), which had a sensitivity of 61% and a specificity of 86% 17 . This study also compared the prognostic performance of a lactate value at admission to PRISM III score and found that the prognostic accuracy of blood lactate for inhospital mortality was similar to that of the PRISM III score.…”
Section: Discussionmentioning
confidence: 99%